Clinical Manifestations and Treatment Outcomes of Syphilitic Uveitis in a Chinese Population - Rui Zhang; Jiang Qian; Jie Guo; Yifei Yuan; Kang Xue; Han Yue; Ling Chen (Journal of Ophthalmology)
Purpose. To describe the clinical manifestations and treatment outcomes of syphilitic uveitis in a Chinese population. Methods. This is a retrospective case series of 15 consecutive patients with syphilitic uveitis treated at a uveitis referral center between 2012 and 2015. Results. Fifteen patients were diagnosed with syphilitic uveitis based on positive serological tests. Nine patients were male. Coinfection with human immunodeficiency virus was detected in two patients. Twenty eyes presented with panuveitis and all patients had posterior involvement. The most frequent manifestations were retinal vasculitis and papillitis, while syphilitic posterior placoid chorioretinitis was only found in three eyes. All patients received systemic penicillin therapy according to CDC guidelines. Nine patients were misdiagnosed before presenting to our center and the delay in treatment with penicillin was associated with poor final visual outcomes (P<0.05). Conclusions. In our series, both male and female were almost equally affected and coinfection of syphilis with human immunodeficiency virus was uncommon. All patients in this study had posterior involvement and the most common manifestations were retinal vasculitis and papillitis. Syphilis should be considered as an important differential diagnosis especially for posterior uveitis and panuveitis. Early diagnosis and appropriate treatment are important for visual prognosis.